1993
DOI: 10.1038/jcbfm.1993.87
|View full text |Cite
|
Sign up to set email alerts
|

Mouse Strain Differences in Susceptibility to Cerebral Ischemia are Related to Cerebral Vascular Anatomy

Abstract: The consequences of cerebral ischemia were studied in three different strains (BDF, CFW, and BALB/C) of mice. The different strains exhibited significant differences in susceptibility to 24-h focal ischemia. Following middle cerebral artery occlusion (MCAO), infarct volumes (mm3) were 5 +/- 3 in BDF, 15 +/- 5 in CFW, and 23 +/- 3 in BALB/C mice (p < 0.05). MCAO plus ipsilateral common carotid artery occlusion (CCAO) resulted in infarct volumes of 15 +/- 9 in BDF, 38 +/- 10 in CFW, and 72 +/- 12 in BALB/C mice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
167
2
1

Year Published

1996
1996
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 270 publications
(182 citation statements)
references
References 25 publications
11
167
2
1
Order By: Relevance
“…In keeping with previous findings (Barone et al, 1993), significant (~50%) pyramidal cell death occurred in the CA1 region of dorsal hippocampus in mice subjected to 6 min of BCCAO. Dead and dying pyramidal cells in the injured hippocampi displayed features of cellular necrosis, characterized in Nissl-stained coronal sections by pyknotic nuclei, irregular cell contours, and loss of nuclear dye retention.…”
Section: In Vivo Neuronal Injurysupporting
confidence: 92%
“…In keeping with previous findings (Barone et al, 1993), significant (~50%) pyramidal cell death occurred in the CA1 region of dorsal hippocampus in mice subjected to 6 min of BCCAO. Dead and dying pyramidal cells in the injured hippocampi displayed features of cellular necrosis, characterized in Nissl-stained coronal sections by pyknotic nuclei, irregular cell contours, and loss of nuclear dye retention.…”
Section: In Vivo Neuronal Injurysupporting
confidence: 92%
“…Because there can be variations in cerebrovascular anatomy between strains of mice which can affect the severity of cerebral ischemic tissue damage, 23 initial experiments were performed to ascertain that the CD18 Ϫ/Ϫ mice did not have grossly detectable variations in cerebrovascular anatomy. For these experiments, an antemortem intravascular injection of India Ink was used to define the Circle of Willis and its principal branches.…”
Section: Resultsmentioning
confidence: 99%
“…The present study also confirms that a decreased level of CuZn-SOD in mutant mice does not affect the residual CBF during ischemia. Recently, Barone et al (1993) reported a significant difference between mouse strains in their sensitivity to focal ischemia that was related to the structural and functional differences in the potency of the circle of Willis. Although the functional vascular anatomy was not examined in the present study, a similar level of CBF decreases during ischemia in Wt and mutant animals clearly suggests that functional vascular anatomy does not play a role in the outcomes after focal cerebral ischemia.…”
Section: Discussionmentioning
confidence: 99%